Freedom of expression in the digital age: enhanced or undermined? The case of Egypt. Issue 1 (2nd January 2018) - Fathy, Noha
ABSTRACT: This research is intended to assess the extent to which freedom of expression is enhanced or undermined in the digital age. The purpose of this investigation is to explore the case study of Egypt. By employing qualitative modes of enquiry, the research argues that the internet could buttress freedom of expression as a ubiquitous, open, global network. However, these potentials are hindered by the violations of the right to freedom of expression carried out by the Egyptian government. To this aim, the study is built on a conceptual framework that hinges on three modalities adopted from Lawrence Lessig's (2006) framework: 1) the law – the internet legislation that regulates online freedoms; 2) the architecture – the design of the internet which is founded on hardware and software, and 3) the social norms – the norms that are imposed by the community and influenced by the law. To investigate these three modalities, three pertinent indicators need to be incorporated: 1) the international human rights standards that enshrine freedom of expression, against which the local legal landscape is assessed; 2) the internet filtering, censorship and surveillance used to analyse the internet architecture, and 3) the encroachments on human rights which would be necessary in order to examine if the social norms were altered by such violations.